Evolución de la mortalidad por neoplasias malignas en Perú. Periodo 2000 – 2023 - Vigo Chacón, Geraldine Judith (2025)
Objective. To analyze the evolution of mortality from malignant neoplasms in Peru, from 2000 to 2023. Method. Epidemiological study, which analyzes the adjusted mortality rates for malignant neoplasms by age group, department and type of neoplasm; trends of the adjusted mortality rates for malignant neoplasms were evaluated by the trend test and the Mann-Kendall tau index obtained from the REUNIS database of the MINSA, during the period 2000 to 2023. Results. There were 745,842 records of deaths due to neoplasms in the period considered, observing that 52.17 % of the deaths due to neoplasm were of women, the most affected age group is that of older adults, with greater prevalence in the departments of Ayacucho and Puno. Conclusions. The trend in adjusted mortality rates for malignant neoplasms has shown a decreasing trend between 2000 and 2023, with a weak decrease in men and a moderate decrease in women. By age group, the population most affected by malignant neoplasms is older adults. By department and type of neoplasm, the overall trend was decreasing.